2015
DOI: 10.1016/j.ejvs.2015.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Part One: For the Motion. Carotid Endarterectomy is Safer than Stenting in the Hyperacute Period After Onset of Symptoms

Abstract: The carotid artery has been a regular battleground for debates regarding many issues, including appropriate management of symptomatic and asymptomatic lesions, the conduct, timing and safety of such interventions, and now whether endarterectomy or stenting is safer in the hyperacute period. Our discussants agree that, as a prophylactic procedure, a carotid intervention should occur early after index symptoms to prevent as many strokes as possible. However, which intervention is best?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The results concerning stenting during the acute period after ischemic stroke are inconsistent: some studies have reported that stenting within 14 days was associated with an excess of procedural risk, whereas other studies concluded that stenting was no worse than endarterectomy. 22,23 None of these studies distinguished between territorial and border-zone CI. Stenting might have better results in border-zone infarcts assuming that most cases of postoperative stroke are due to embolic mechanisms from unstable plaques, which could be less frequent in hemodynamic border-zone infarcts than in embolic territorial infarcts.…”
Section: Discussionmentioning
confidence: 99%
“…The results concerning stenting during the acute period after ischemic stroke are inconsistent: some studies have reported that stenting within 14 days was associated with an excess of procedural risk, whereas other studies concluded that stenting was no worse than endarterectomy. 22,23 None of these studies distinguished between territorial and border-zone CI. Stenting might have better results in border-zone infarcts assuming that most cases of postoperative stroke are due to embolic mechanisms from unstable plaques, which could be less frequent in hemodynamic border-zone infarcts than in embolic territorial infarcts.…”
Section: Discussionmentioning
confidence: 99%